SportWatch: Sports activities wearable monitoring and coaching - Carlos David Lopes Clemente (2016)
Recently, with the great evolution of cinematic and mechanical study of Human body, there is an increasingly need to collect new data concerning this issue. In a company like Kinematix Sense it's essential that the users of its technology feel comfortable, above all matters. Following this requirement and the growing evolution of the market for wearables, devices capable of capturing innovative parameters that bring great value for this type of study and also for the users, were developed. The importance of the parameters collected in running, both in terms of performance and in terms of injury prevention, is studied. It is also made an analysis of the currently most popular method used for observing the running technique. As the system developed by the company Kinematix Sense depend on a smartphone (to receive data from the sensors) and taking into to account that a device of this nature will always be uncomfortable for running practice, it would be a great advance if this function could be made by a device with smaller dimensions. With the evolution of the wearables market, specifically smartwatches, there are already small devices capable of replacing smartphones. This research aims to develop a prototype of an application to smartwatch to be able to replace the smartphone during the collection of the parameters from the TUNE devices. The development of the prototype was made in Android Wear for a specific smartwatch, the "Sony Smartwatch 3" which, upon the initiation of this research, was the only equipped with an integrated GPS antenna. The prototype should also be able to display the sensors state in real time, capture GPS positions along the way and display the information about the data acquired.